Perancangan dan Analisis Sistem Komunikasi Serat Optik Link Makassar-Maumere Menggunakan DWDM - Fitria Ayu Nurdiana; Sugito; Sofia Naning Hertiana (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Today, the Palapa Ring project launched by the government is focused on development in Eastern Indonesia. The fiber optic is chosen for backbone network because fiber optics have wide bandwidth, thus allowing delivery of messages on various services. This study designs an optical backbone network for connecting Makassar and Maumere. This design uses several parameters, both technical and non-technical, such as human activities and sea conditions connecting the two regions. This design also uses the power link budget and the rise-time budget as reliability parameters. The results show that maximum BER is 5.892 x 10-11, which is still below the standard, 10-9.